EXPRESSION PATTERNS OF AN ABIOTIC STRESS-INDUCIBLE DEHYDRATION RESPONSIVE ELEMENT BINDING PROTEIN-2 (DREB2) GENE IN TOMATO (Bangladesh Journal of Plant Breeding and Genetics, 2012)
A novel DREB (dehydration-responsive element binding) gene, designated as LeDREB2, was isolated from tomato. Based on multiple sequence alignment and phylogenetic characterization, LeDREB2 gene was classified into an A-2 group member of the DREBs family. We examined the expression pattern of LeDREB2 gene in tomato under different abiotic stresses. Southern blot analysis showed that LeDREB2 is a single copy gene in tomato genome. The organ specific expression profiling indicated that LeDREB2 gene was strongly expressed in young leaves and roots but weak expression in mature leaves and shoots. Northern blot analysis revealed that various kinds of environmental stress such as salt, drought and cold were significantly induced by LeDREB2 gene after application of time courses treatments except little increase in ABA. Our findings showed that the expression of LeDREB2 gene was induced by high salinity, drought and cold but not by the abscisic acid (ABA) treatment. These results indicated that the LeDREB2 gene is a member of the DREB transcription factors, which may play a role in both abiotic and oxidative stress responses.DOI: http://dx.doi.org/10.3329/bjpbg.v25i1.17006